Assessment of psoriasis severity in Brazilian patients with chronic plaque psoriasis attending outpatient clinics: a multicenter, population-based cross-sectional study (APPISOT) - Romiti, Ricardo; Zambaldi Fabricio, Lincoln Helder; Souza, Cacilda da Silva; Galvao, Leticia Oba; Silva de Castro, Caio Cesar; Terena, Aripuana Coberio; Oliveira Carneiro, Francisca Regina; Matsuka Oyafuso, Luiza Keiko; Carneiro, Sueli; Gontijo, Bernardo; Kobata, Clarice Marie; Paim de Oliveira, Maria de Fatima; et al. (Taylor & Francis Ltd, 2018)
Purpose: Data on chronic plaque psoriasis severity and its potential clinical and lifestyle implications in the Brazilian population are limited. The primary aim of this study was to assess the clinical severity of plaque psoriasis in Brazil. Further objectives included evaluating potential associations between disease severity and demographic, lifestyle, and clinical characteristics, health-related quality of life (HRQOL), and work productivity. Materials and methods: This observational (non-interventional) cross-sectional study was conducted in 26 dermatologic clinics across 11 Brazilian states. Psoriasis severity was assessed using investigator judgment and Finlay's Rule of Tens: a Psoriasis Area and Severity Index (PASI) score >10, a Body Surface Area (BSA) > 10%, or a Dermatology Life Quality Index (DLQI) score >10. Results: Among 1125 patients, 205 (18.2%) had moderate-to-severe disease. On multiple regression analyses, psoriasis severity was significantly (directly) associated with the presence of physical inactivity and comorbid pain, anxiety, and depression; and significantly (inversely) associated with HRQOL and work productivity. Limitations: Cross-sectional studies cannot assess temporal trends, and observational studies cannot conclusively determine causality or exclude biases and confounding due to unmeasured variables. Conclusions: Among Brazilian patients with moderate-to-severe psoriasis, disease severity had far-reaching adverse impacts on lifestyle, comorbidities, HRQOL, and work productivity.
Keywords: Epidemiology; health-related quality of life; pain; psoriasis; severity; worker productivity